Hepatic Splenosis: A Rare Entity and Great Mimicker - Shruthi KB; Hanan PK (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Splenosis is a benign and rare condition that is usually caused by trauma or splenectomy or other procedures involving splenic tissue. The patient is usually asymptomatic and often diagnosed incidentally especially when presents as intrahepatic lesion, can be misdiagnosed as neoplasm. Here, we present case report of a 56-year-old male patient, who was incidentally detected to have focal liver lesion on routine ultrasound check up. He was further evaluated with computed tomography (CT) and magnetic resonance imaging (MRI) and the lesion was indistinguishable from neoplastic lesions and misdiagnosed to be hepatic adenoma. Retrospectively analyzing, the patient had history of splenectomy following road traffic accident 10 years before the present presentation. Following laparotomy, the liver lesion was resected and histopathology confirmed the diagnosis of hepatic splenosis. In this case report and review, we present the diagnostic features and the criteria that help in the diagnosis of splenosis which is a great mimicker.